Relaunching Laboratories for Engineering Disciplines Using an Industry-Oriented Approach - Dinu, Alexandru; Ghiocanu, Stefania Cristina; Modran, Horia Alexandru (SC LUMEN MEDIA SRL, 2024)
A pleasant working environment starts with a smooth adjustment of the graduate to the workplace. For this reason, preparing students in line with companies' work requirements must be in the focus during faculty. Since many of the subjects currently taught do not take this into account, this paper aims to contribute validated ideas and techniques to the creation of industry-oriented teaching activities. Therefore, this paper presents how practical work at a laboratory in an IT faculty has been adapted to accommodate some important aspects encountered in companies and required from future employees: teamwork where each member has well-defined tasks, creativity, taking on the task at hand, using cloud-hosted tools, tracking tasks within a team using dedicated platforms, and logging and solving a bug in a professional way. Actively helping the students in acquiring the necessary skills to design and verify a part of a chip, several didactic methods (e.g. brainstorming, explanation, discussion, “jigsaw” method) were also used to lead the students, step by step, to a good understanding of the working environment in a corporation. As results, it is shown that the students managed to learn how to approach the specific tools and methods of a company, and the good quality of the products obtained was confirmed by representatives of several companies in the field. The students' views on the teaching process, collected through an anonymous questionnaire, are also deeply analysed and discussed. Finally, the paper highlights the main aspects that positively influenced the students' professional development during teaching activities.
Keywords: collaborative learning; didactic methods; graduates adjustment to the workplace; industrial approaches in education; cloud-hosted tools